Association of Body Mass Index with Physical Function and Health-Related Quality of Life in Adults with Arthritis. (12th December 2013) - Schoffman, Danielle E.; Wilcox, Sara; Baruth, Meghan
Abstract : Arthritis and obesity, both highly prevalent, contribute greatly to the burden of disability in US adults. We examined whether body mass index (BMI) was associated with physical function and health-related quality of life (HRQOL) measures among adults with arthritis and other rheumatic conditions. We assessed objectively measured BMI and physical functioning (six-minute walk, chair stand, seated reach, walking velocity, hand grip) and self-reported HRQOL (depression, stiffness, pain, fatigue, disability, quality of life-mental, and quality of life, physical) were assessed. Self-reported age, gender, race, physical activity, and arthritis medication use (covariates) were also assessed. Unadjusted and adjusted linear regression models examined the association between BMI and objective measures of functioning and self-reported measures of HRQOL. BMI was significantly associated with all functional (P s ≤ 0.007 ) and HRQOL measures (P s ≤ 0.03 ) in the unadjusted models. Associations between BMI and all functional measures (P s ≤ 0.001 ) and most HRQOL measures remained significant in the adjusted models (P s ≤ 0.05 ); depression and quality of life, physical, were not significant. The present analysis of a range of HRQOL and objective measures of physical function demonstrates the debilitating effects of the combination of overweight and arthritis and other rheumatic conditions. Future research should focus on developing effective group and self-management programs for weight loss for people with arthritis and other rheumatic conditions (registered on clinicaltrials.gov: NCT01172327 ).